Attitude towards Working in Rural Areas among Nursing Students in a Medical College of Kaski District - Kandel, Kritika; Silwal, Muna; Gurung, Rajmi (HPE Forum, 2025)
Nursing manpower shortage is a worldwide problem and it is vital for a nation to have nurses in all level of the health care delivery system. This study aims to assess the attitude towards working in rural areas after graduation among nursing students of Kaski. A descriptive cross-sectional research design was adopted for the study which was conducted in Gandaki Medical College; Rithepani among 75 undergraduate female nursing students of Gandaki Medical College. Total enumerative sampling technique was used. Structured self-administered questionnaire was used to collect data. Data were analyzed by employing both descriptive (frequency, mean, standard deviation) and inferential statistical methods (Chi-square test). The p≤0.05 was considered statistically significant. The study found that more than half (53.3%) of the respondents had positive attitude. However, nearly half (46.7%) had negative attitude towards working in rural areas after graduation. There was statistically significant association of age (p=0.04) and having a family member in rural service (p=0.02) with attitude towards working in rural areas after graduation. Nursing students of age less than 24 years (65.7%) and those with their family member in rural service (72.0%) were more likely to choose working in rural areas after graduation. Nearly half of nursing students had negative attitude to work in rural areas after graduation. This study concludes that having a family member in rural service and those with age less than 24 years had positive attitude to rural service.